Decolorization of Peat Water by Catalytic Ozonation Process - Hikmatussa'diah, Sofia; Adityosulindro, Sandyanto; Qadafi, Muammar; Laksono, Sucipta (Proceedings of the International Conference on Green Technology; Vol 14 No 1 (2024): Proceeding of 14th International Conference on Green TechnologyDO - 10.18860/icgt.v14i1.3220, 2024)
Peat water is a potential source of raw water in Indonesia, especially on the island of Kalimantan. However, the high concentration of natural organic matter, color, dissolved iron, and low pH in peat water is challenging for conventional water treatment systems such as coagulation-flocculation. This work investigated ozonation-based processes as potential pre-treatment for color and organic removal. Experimental comparisons were made between O3, O3/UV, O3/Fe, and O3/UV/Fe to analyze the effect of UV and iron catalysts on the effectiveness of the ozonation process. The most promising result was obtained in the O3/UV/ZVI process at pH 5 with initial conditions including stirring speed during ozonation 300 rpm, temperature 27°C, system volume 250 mL, and ZVI catalyst dosage (1 g/L) with a continuous process for 60 minutes. O3/UV/ZVI was able to color removal (77%), COD (72%), and total Fe (90%). In addition, the figure-of-merit of studied processes was carried out through Electric Energy per Order (EEO). In conclusion, the catalytic ozonation process as a pre-treatment proved efficient for removing color, organic compounds, and neutralizing pH.